The manipulation of progesterone profiles during progesterone + estradiol timed ai protocols in dairy cattle: effects on fertility - Pereira, Marcos Henrique Colombo [UNESP] (2016)
Study 01- Our hypothesis was that fertility could be increased in a timed AI (TAI) protocol based on estradiol (E2) and progesterone (P4) by combining GnRH with E2-benzoate at the start of the protocol to increase circulating P4 concentration during preovulatory follicle development and by using two prostaglandin (PGF) treatments at the end to decrease circulating P4 concentration near TAI. Lactating Holstein cows (n = 1,808) were randomly assigned during the cool or hot seasons of the year to receive TAI (d0) following one of three treatments: I. Control: CIDR + 2 mg of E2-benzoate on d -11, PGF on d -4, CIDR withdrawal + 1.0 mg of E2-cypionate on d -2, and TAI on d 0; II. 2PGF: Identical to Control protocol with addition of a second PGF treatment on d -2; III. GnRH: Identical to 2PGF protocol with addition of 100 μg GnRH treatment on d -11. Pregnancy diagnoses were performed d32 and d60 after TAI. The GnRH protocol increased percentage of cows with CL (Control = 56.9%; 2PGF = 55.8%; GnRH = 70.5%) and circulating P4 concentration at PGF (Control = 3.28 ± 0.22; 2PGF = 3.35 ± 0.22; GnRH = 3.70 ± 0.21 ng/mL), compared to Control and 2PGF protocols. The positive effects of GnRH treatment on P/AI were only detected during the cool season (GnRH = 50.9%; 2PGF = 44.2%; Control = 41.0%) and not during the hot season. In addition, the effect of GnRH was only observed in cows with low circulating P4 concentration (<3ng/mL) at the start of the protocol and not in cows that began the protocol with high P4. Further, there was an interaction for presence of CL at PGF with follicle diameter such that cows with a CL at PGF had greater P/AI if they ovulated larger rather than smaller follicles near TAI.Season had major effects on many reproductive measures with cool season greater than hot season in percentage of cows with CL at PGF (62.9 vs. 56.2%), ovulatory follicle diameter (15.7 vs. 14.8 mm), expression of estrus (86.7 vs. 79.9%), ovulation following the protocol (89.7 vs. 84.3%), and pregnancies per AI (P/AI; 45.4 vs. 21.4%). Thus, fertility to TAI can be improved by inducing ovulation at the 27 beginning of an E2/P4-based protocol using GnRH treatment, particularly during the cool season of the year and in cows with low P4 at the start of the protocol. Study 02- We hypothesized that the 2 CIDR protocol would have similar results on circulating P4 concentration at PGF, ovulation to ECP, P/AI, and pregnancy losses. Lactating Holstein cows (n = 1,638) were randomly assigned to receive TAI (d0) following one of two treatments: (I. GnRH treatment) CIDR+ 2 mg of E2-benzoate + 100 μg GnRH on d -11, PGF on d -4, CIDR withdrawal + 1.0 mg of E2-cypionate + PGF on d -2, and TAI on d 0; (II. 2CIDR treatment) Two CIDR + 2mg of E2-benzoate on d -11, one CIDR withdraw + PGF on d -4, second CIDR withdrawal + 1.0 mg of E2-cypionate + PGF on d -2, and TAI on d 0. Pregnancy diagnoses were performed d32 and d60 after TAI. There was no effect of treatments (P > 0.10) on fertility regardless of cow temperature, BCS, parity, milk yield and presence or absence of a CL on d -11 or d -4. Some physiological measurements associated with greater fertility were reduced in cows with elevated temperature (≥ 39.1ºC) as percentage of cows with CL at PGF decreased 5.4%, ovulatory follicle diameter decreased 0.51 mm, expression of estrus decreased 4.7%, and ovulation to the ECP decreased 2.5% compared to cows with reduced temperature (< 39.0ºC), with result in 13.4% decrease (P < 0.01) in P/AI and tended to increase (P = 0.09) the pregnancy loss between 32 and 60d. There were more (P < 0.01 ) cows with a CL at PGF in the GnRH (< 39.0ºC = 78.1% [314/402]; ≥ 39.1ºC = 70.9% [256/361]) protocol than in 2CIDR protocol (< 39.0ºC = 58.8% [244/415]; ≥ 39.1ºC = 54.6% [190/348], however, circulating P4 concentration was greater (P = 0.05) at the time of PGF treatment (d -4) for cows treated 2CIDR (< 39.0ºC = 4.34 ± 0.13; ≥ 39.1ºC = 4.17 ± 0.14 ng/mL) than GnRH (< 39.0ºC = 4.12 ± 0.14; ≥ 39.1ºC = 3.84 ± 0.14 ng/mL), independent of cow temperature. The result of this study shows that the protocols have similar results on circulating P4 concentration at PGF, ovulation to ECP and P/AI.